Intructional Leadership to Realize School Quality Culture (Case Study at Insan Amanah Elementary School, Malang City) - Adriansyah, Riko Rahmad; Yusuf Sobri, Ahmad; Bambang Sumarsono, Raden; Wahiza binti Abdul Wahat, Nor (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
This study aims to describe the profile of Intructional leadership in establishing a quality culture. This research was conducted using a qualitative approach, and the research design was a case study. The research was carried out at SD Insan Amanah in Malang City, which is a private elementary school with an A accreditation and has achieved various academic and non-academic achievements. Conclusions drawn from data analysis are: (1) the profile of Intructional leadership focuses on overall quality improvement in various areas and continuous improvement; (2) the strategies of Intructional leadership in establishing a culture of quality involve shared perception and creating a harmonious work environment; (3) the forms of quality culture include school culture and Islamic culture, six dimensions of Pancasila student profiles, and a reward and punishment system; (4) the supporting factors of Intructional leadership in establishing a quality culture involve the participation of all school members and collaboration; and (5) the inhibiting factors include demotivated staf, less enthusiastic students, unsupportive community, excessive administrative burden, and simultaneous school programs. However, the headmaster has implemented various measures to address these issues, such as promptly solving problems, conducting weekly reflection activities, periodic monitoring and guidance, coaching clinics, and maximizing the role of guidance and counseling teachers.